Black Cisgender Women's PrEP Knowledge, Attitudes, Preferences, and Experience in Chicago. (15th August 2020) - Hirschhorn, Lisa R.; Brown, Rayna N.; Friedman, Eleanor E.; Greene, George J.; Bender, Alvie; Christeller, Catherine; Bouris, Alida; Johnson, Amy K.; Pickett, Jim; Modali, Laxmi; Ridgway, Jessica P.
Abstract : Background: Although black cisgender women in Chicago continue to disproportionally account for new HIV diagnoses, few are on pre-exposure prophylaxis (PrEP). We used concurrent mixed-methods to understand women's PrEP knowledge, attitudes, experience, and preferences in Chicago. Setting and Methods: We surveyed 370 HIV(−) cisgender women visiting a sexually transmitted infection clinic (n = 120) or emergency department (n = 250). Two focus groups were conducted with PrEP-naive women, and interviews were conducted with 7 PrEP-experienced women. Quantitative data were analyzed using descriptive statistics and multivariable logistic regression, and qualitative data using thematic analysis. Results: Majority of women identified as black (83.0%) and had a regular source of health care (70.0%). In the past 6 months, 84.1% had vaginal or anal sex, most with inconsistent condom use (94.2%). Only 30.3% had heard of PrEP, but once explained, one-quarter considered starting PrEP, with protecting health (76.4%) and reducing HIV worry (58.1%) the most common reasons. Factors associated with considering PrEP included being Latina [adjusted odds ratio (aOR): 3.30, 95% confidence interval (CI): (1.21 to 8.99)], recent sexually transmitted infection [aOR: 2.39, 95% CI: (1.25 to 4.59)], and higher belief in PrEP effectiveness [aOR: 1.85, 95% CI: (1.22 to 2.82)]. Most (81.1%) had concerns about taking PrEP with side effects a common concern. Qualitative themes aligned with survey results, revealing a disconnection from current PrEP marketing, need for community-level PrEP education/outreach, and importance of provider trust. Lessons Learned: Despite significant PrEP implementation work in Chicago, less than one-third of women in our study had heard of PrEP. Once informed, PrEP attitudes and interest were positive. Translating these results into interventions reflecting women's preferences and barriers is critical to increase PrEP uptake by cisgender women in Chicago and elsewhere. Abstract : Supplemental Digital Content is Available in the Text.